Development of Flipbook-Based E-Module on Animalia Material as Teaching Material to Train Digital Literacy of Class X High School Students - Nidya Ismiya Ningrum; Reni Ambarwati (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2023)
Digital literacy is a necessary skill for students to enter the 21st century education era. The research aimed to provide an electronic module of Animalia material to train digital literacy for class X high school students which is valid and practical. This research refers to the 4-D development model (Define, Design, Development, and Disseminate) without disseminate. The validity of the e-module was measured based on the feasibility of contents, the feasibility of presentation and the suitability of the E-Module with the characteristics of the module and digital literacy indicators by education experts and material experts. The practicality of the E-Module was measured based on a readability test utilizing the fry graph, implementation at the limited trial, as well as the response of Biology teachers and class X High School students to E-Modul Animalia. Descriptive-quantitative analysis was applied to the data. The results showed that the Animalia E-Module was very valid, with an overall score of 100%. E-Modules can be deemed practical with the results of the readability test according to the student’s grade level, namely level 10, the findings of the observation of learning implementation yielded a score of 100 %, signifying that the Animalia E-Module is being utilized very effectively in addition to the acquisition of results from teachers’ and students’ responses comprising 96% and 95%, respectively. Therefore, it can be concluded that the Animalia E-Module is very valid, practical and feasible for use in learning. Keyword: Online learning, evaluation content, Animalia